Automatic assemblies design using AUTOCAD and AUTOLISP software packages - Gatalo, Ratko; Hološi, Zoltan; Navalušić, Slobodan; Zeljković, Milan (Journal of Production Engineering, 1992)
In this article, we delve into a system for automatic assembly design employing the AutoCAD software package and the AutoLISP programming language. We kick off by discussing the outcomes achieved through automating specific design phases of products, as implemented at the Institute for Production Engineering in Novi Sad. Our primary focus is on the automation of assembly design, with a particular emphasis on a gearbox (referred to as "sear box"). We then provide a detailed overview of the various phases involved in this process, including drawing preparation, menu selection, AutoCAD command selection, and geometrical shape selection. Furthermore, we offer insights into the information base, which consists of two distinct parts: elements defined by geometrical shapes and elements defined by AutoLISP programs. We also explore the design phases at the single-shaft level, highlighting the need to repeat these phases for each shaft of the gearbox. To conclude, the article showcases some of the results obtained from testing this system for automatic assembly design.